Co-culturing a multistrain Gram-negative inoculant useful in sustainable agriculture - Farda, Beatrice; Pasquarelli, Fabrizia; Djebaili, Rihab; Spera, Daniela M.; Del Gallo, Maddalena; Pellegrini, Marika (Frontiers in Industrial Microbiology, 2024)
Microbial-based inoculants for agricultural use consist of different strains. The consortia production process involves growing pure cultures separately and combining them in the appropriate ratio. However, the inclusion of multiple strains in the formulation increases production costs. By developing co-culture fermentations, it is possible to create consortia with the correct bacterial charge. This study aims to develop a cost-effective co-culture approach for producing an inoculum that includes the appropriate ratio of four Gram-negative bacteria, i.e., Azospirillum brasilense, Burkholderia ambifaria, Gluconacetobacter diazotrophicus, and Herbaspirillum seropedicae. The specific growth rates of strains were studied using the T4 medium, previously optimized for their culture. The co-fermentation process was optimized in 500 mL flasks to attain an equivalent density of 9.7-10 Log CFU mL-1. Then, it was successfully scaled up to a 5 L bioreactor, obtaining an equivalent density of 9.7-9.9 CFU mL-1. This first co-formulation of a four multistrain consortium formed by Gram-negative plant growth-promoting bacteria pave the road for future evaluations of other products useful for sustainable agriculture.